Pengaruh Kualitas Produk dan Harga Pupuk Subsidi terhadap Minat Beli Konsumen Kelompok Tani Desa Ipar Bondar Kecamatan Panyabungan Kabupaten Mandailing Natal - Juni Soleha Btr; Muhlisah Lubis; Sari Fitri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This research is motivated by the important role of subsidized fertilizer in increasing agricultural productivity and supporting national food security. However, in Ipar Bondar Village, Panyabungan District, Mandailing Natal Regency, problems related to fertilizer availability, farmers' perceptions of product quality, and price fluctuations still exist that affect consumer purchasing interest in farmer groups. In this context, product quality and price are the main factors that can influence farmers' decisions in purchasing subsidized fertilizer. Therefore, this study was conducted to analyze the extent of the influence of product quality and price on consumer purchasing interest in farmer groups in the area. Based on this, this study aims to determine the extent of the influence of product quality and price on purchasing interest in subsidized fertilizer in farmer groups in Ipar Bondar Village. This study uses a quantitative approach with a descriptive research type. The population of this study was all members of farmer groups using subsidized fertilizer in Ipar Bondar Village, with a sample size of 113 respondents. The sampling technique used was random sampling. Data collection was carried out through a questionnaire compiled using a Likert scale. The data was then analyzed using validity and reliability tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²) using SPSS 25. The results showed that, partially, product quality had a positive and significant effect on purchase intention for subsidized fertilizer. This means that the better the perceived quality of the fertilizer, the higher the farmer's purchase intention. Similarly, price also had a positive and significant effect on purchase intention. Simultaneously, both variables significantly influenced purchase intention, with a determination value of 0.806%. This means that product quality and price together significantly influence farmers' purchase intention for subsidized fertilizer. The results of the study concluded that product quality and price play a significant role in increasing purchase intention for subsidized fertilizer.